The Framework for Audits of the Financial Statements of the Group of Enterprises by ISA 600 Requirements - V. P. PANTELEIEV (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
Compliance with relevant regulations is the basis of the professional activities of auditors. Users of financial statements require the auditor to conduct quality audit. The auditor’s opinion on the reliability of the financial statements of the group is based on the application of appropriate audit approaches, based both on audit practice and audit standards, and insist on compliance with recognized audit requirements.The aim of the article is to highlight the content of the main rules for an independent auditor to audit the financial statements of a group using the requirements of the modern regulatory framework, in particular International Standard of Auditing (ISA) 600.The essence of the main rules of an independent auditor conducting an audit of a group’s financial statements using the requirements of the modern regulatory framework, in particular ISA 600, is disclosed. The need for regulation of an audit of a group’s consolidated financial statements is formulated, the content and important provisions of the requirements of a professional standard ISA 600 “Special Considerations – Audits of group financial statements (including the work of component auditors)”. Interpretation of the requirements of ISA 600 for acceptance and continuation of the assignment, the role of the auditor’s assessment of distortions during the audit, audit activities to prevent, detect and combat fraud in the group, the obligation to use the component of the level of distortion by the auditor is given. The author’s vision of the special provisions of the audits of the financial statements of the group is indicated, the sequence of advancing audit procedures in the implementation of the special provisions of the audits, including the work of the component auditors, and the directions for further research are shown. Conclusions. The responsibility of the auditor and the component auditor is envisaged, and atypical relevant measures are required in response to challenges; the auditor deals with complex structures, the information of the component auditors must be taken into account. ISA 600 is connected with other audit standards, it regulates a number of requirements with the aim of conducting a quality audit of the group financial statements: from the responsibility of the auditor, accepting and continuing the assignment, developing a general audit strategy and plan, understanding of the component auditor, communicating information to the group’s management personnel and those who endowed with high authority at the group level, etc. documentation. The peremptory question of ISA 600 is determining whether he should act as an auditor of the group financial statements, that is, reasonably refuse or accept the assignment; and if accepted and continued, the task if he acts as an auditor of the group financial statements: communication of clear information to the component auditors on the volume and time of their work with financial information relating to the components and the actual results obtained by them; obtaining sufficient audit evidence in sufficient amounts on the financial information of the components and the consolidation process to express an opinion that the group’s financial statements have been prepared in all material respects in accordance with the applicable financial reporting framework.